Yield and technological characteristics of common bean fertilized with nitrogen and molybdenum - Silva, Tiago Roque Benetoli da (2006)
The objective of this work was to evaluate the effect of nitrogen and molybdenum fertilization on the yield and technological characteristics of common bean. The experiment was carried out in a randomized blocks design, in a factorial outline of 4x2, constituted by nitrogen side-dressing levels (0, 30, 60 and 120 kg ha-1), with or without molybdenum leaf application (0 and 80 kg ha-1), with four replications. The Pérola cultivar was sowed in growing season, in no-tillage system. The nitrogen side-dressing and molybdenum application do not affect common bean yield, but influence the technological characteristic of the grains. The protein content, the coocking time, and time for maximum hydration increase with nitrogen side-dressing levels increment. The cocking time is high for nitrogen side-dressing with molybdenum use. The use of molybdenum promotes the maximum grain hydration in the minimum time.